Packing density and message traffic density of a midimew connected mesh network - Rahman, M.M. Hafizur; Al Faisal, Faiz; Mohd Nor, Rizal; Tengku Sembok, Tengku Mohd; Akhand, M. A. H.; Inoguchi, Yasushi (IEEE, 2016)
Interconnection network topology is a pivotal factor in the performance and reliability of the parallel computer system ranging from multiprocessor to massively parallel computers (MPC). Hierarchical network topology yields better performance with low cost by exploring the locality in the communication and traffic patterns. A Midimew connected Mesh Network (MMN) is a hierarchical interconnection network comprised of numerous basic modules, where the basic module and higher level network of hierarchy is a 2D-mesh and a midimew networks, respectively. In this paper, we present the architecture of MMN and evaluate the packing density and message traffic density of MMN, TESH, mesh, and torus networks. It is revealed that the proposed MMN yields high packing density and low message traffic density which will results efficient VLSI realization and high communication performance of the MMN. Overall, performance with respect to packing and densities reveals that the MMN will be a promising choice for next generation MPC systems.